Characterization of Raw and Alkali Treated Cellulosic Filler Isolated from Putranjiva roxburghii W. Seed Shell Roadside Vegetative Residues. Issue 16 (28th November 2022) - Muthukrishnan, K.M.; Selvakumar, G.; Narayanasamy, P.; Ravindran, P.
ABSTRACT: A natural cellulosic filler extracted from the seed shells of the Putranjiva roxburghii W. has been investigated for its suitability in reinforcement of fiber reinforced polymers. The physicochemical, morphological, structural, and thermal properties of untreated and alkali-treated Putranjiva roxburghii seed shell filler (PRSSF) particles are investigated for the first time. The particle size and morphology of PRSSF particles have been analyzed using laser particle size analyzer and field emission scanning electron microscopy. Energy-dispersive X-ray spectroscopy was used to validate the elements present on the untreated and treated PRSSF particles. The structural features were investigated using X-ray Diffraction, nuclear magnetic resonance, and Fourier transform infrared spectroscopy analysis, which revealed the reduction of the amorphous contents and noncellulosic components. Thermogravimetric analysis was employed to determine the thermal stability of both untreated and treated PRSSF particles. The results indicated that alkali-treated PRSSF particles have higher thermal degradability and stability than untreated PRSSF particles.